Effects of Haemodialysis on Red Cell Indices and Haematocrit in Chronic Kidney Disease Patients - Chowdhury, Mohammed Nasim Uddin; Khatun, Monira; Dutta, Pradip Kumar; Akhter, Nayeema (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background: Chronic Kidney Disease (CKD) is an escalating public health problem throughout the developed and developing world. Haemodialysis influences the transport of water through the erythrocyte membrane and induces morphologic and functional modifications. Objective: This study is aimed at to show the effects of haemodialysis on red cell indices and haematocrit in Chronic Kidney Disease (CKD) patients receiving Maintenance Haemodialysis (MHD) during haemodialysis (HD) process in their post-dialysis blood samples. Methods: It is a Hospital based, crosssectional comparative study. The study population consisted of 40 patients of diagnosed case of chronic kidney disease patients on haemodialysis in the Department of Nephrology, Chittagong Medical College Hospital, Chittagong. The haematological changes before and after the ending of haemodialysis procedure were studied by complete blood count study by automated analyzer. Data were analyzed by statistical methods (Paired sample t-test). Results: In our study the predialysis and post-dialysis sample showed the mean(±SD) MCV(fl) was 96.20(±11.57)fl and 92.80(±10.75)fl respectively. This shows highly significant difference between mean of pre-dialysis and post-dialysis MCV(fl) level (p=0.001). In pre-dialysis and post-dialysis sample the mean(±SD) MCH(pg) was 29.10(±3.62)pg and 28.79(±3.77)pg respectively. This shows no significant difference between mean of pre-dialysis and post-dialysis MCH(pg) level (p=0.236). In pre-dialysis and post-dialysis sample the mean(±SD) MCHC(g/dL) was 29.25(±3.69)g/dL and 30.25(±3.57) gm/dL respectively. This shows highly significant difference between mean of pre-dialysis and post-dialysis MCHC(g/dL) level (p=0.003). In pre-dialysis and post-dialysis sample the mean(±SD) Haematocrit/PCV(%) was 26.46(±7.34)% and 27.39(±8.07)% respectively. This shows no significant difference between mean of pre-dialysis and post-dialysis Haematocrit/PCV(%) level (P=0.157). Conclusion: The results of this study revealed that significant morphological changes, specially, regarding MCV occurs in patients receiving MHD during HD process in their post-dialysis blood samples along with consequent changes in MCHC. And all these findings are consistent with each other. Chatt Maa Shi Hosp Med Coll J; Vol.16 (1); Jan 2017; Page 15-18